Step
*
1
of Lemma
separated-decider-not-extensional2
1. a : ℝ
2. b : ℝ
3. a < b
4. d : ∀u:ℝ. ((a < u) ∨ (u < b))
5. ∀x,y:ℝ.  ((x = y) 
⇒ isl(d x) = isl(d y))
⊢ ¬(∃x,y:ℝ. ((x = y) ∧ (↑isl(d x)) ∧ (↑isr(d y))))
BY
{ ((D 0 THENA Auto) THEN ExRepD) }
1
1. a : ℝ
2. b : ℝ
3. a < b
4. d : ∀u:ℝ. ((a < u) ∨ (u < b))
5. ∀x,y:ℝ.  ((x = y) 
⇒ isl(d x) = isl(d y))
6. x : ℝ
7. y : ℝ
8. x = y
9. ↑isl(d x)
10. ↑isr(d y)
⊢ False
Latex:
Latex:
1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  a  <  b
4.  d  :  \mforall{}u:\mBbbR{}.  ((a  <  u)  \mvee{}  (u  <  b))
5.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  isl(d  x)  =  isl(d  y))
\mvdash{}  \mneg{}(\mexists{}x,y:\mBbbR{}.  ((x  =  y)  \mwedge{}  (\muparrow{}isl(d  x))  \mwedge{}  (\muparrow{}isr(d  y))))
By
Latex:
((D  0  THENA  Auto)  THEN  ExRepD)
Home
Index